Analisis Kualitas Layanan Pada Platform Keuangan Terhadap Kepuasan Pengguna Menggunakan E-Servqual - Kurniawan, Alfin; Faradillah; Yulianti, Evi (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study analyzes the dominant dimensions of service quality affecting user satisfaction with the financial platform application in Palembang using the E-SERVQUAL method. Conducted quantitatively, the research involved 114 active financial platform users selected through purposive and snowball sampling. Data were collected via an online questionnaire measuring seven E-SERVQUAL dimensions: Efficiency, Fulfillment, System Availability, Privacy, Responsiveness, Compensation, and Contact. Analysis using SmartPLS 4.1.0.9 revealed Efficiency as the most dominant dimension (coefficient 0.266, p=0.000), followed by Privacy (0.236, p=0.001) and Contact (0.211, p=0.002), significantly influencing user satisfaction. In contrast, System Availability and Responsiveness showed no significant impact (p>0.05). These findings indicate that users prioritize transaction speed, ease of navigation, and data security over system uptime or customer service responsiveness. Most respondents were aged 18-25 (66.4%), with high school education (60.3%) and a monthly income below IDR 3 million (48.3%). The study recommends that the financial platform optimize application efficiency, enhance data protection, and improve customer service accessibility to boost user satisfaction. These insights provide a foundation for fintech platforms to refine digital services, particularly in tier-2 cities like Palembang.